Tensor Product of Vector Spaces
📂Linear Algebra Tensor Product of Vector Spaces Buildup For convenience, this exposition is developed for the complex number space C \mathbb{C} C , but it is applicable to R \mathbb{R} R or any vector space as well. Let’s denote the set of functions from a finite set Γ \Gamma Γ to the complex number space as described by C Γ \mathbb{C}^{\Gamma} C Γ .
C Γ = { f : Γ → C }
\mathbb{C}^{\Gamma} = \left\{ f : \Gamma \to \mathbb{C} \right\}
C Γ = { f : Γ → C }
Let’s set Γ \Gamma Γ as n = { 1 , 2 , … , n } \mathbf{n} = \left\{ 1, 2, \dots, n \right\} n = { 1 , 2 , … , n } . A function that sends each 1 ≤ i ≤ n 1 \le i \le n 1 ≤ i ≤ n to a complex number z i ∈ C z_{i} \in \mathbb{C} z i ∈ C is denoted by ( z 1 , … , z n ) (z_{1}, \dots, z_{n}) ( z 1 , … , z n ) , which belongs to C n \mathbb{C}^{\mathbf{n}} C n and is also equivalent to a vector in the complex number ordered pair set C n \mathbb{C}^{n} C n .
( z 1 , … , z n ) : i ↦ z i
(z_{1}, \dots, z_{n}) : i \mapsto z_{i}
( z 1 , … , z n ) : i ↦ z i
C n : = C n = { ( z 1 , … , z n ) ∣ z i ∈ C }
\mathbb{C}^{n} := \mathbb{C}^{\mathbf{n}} = \left\{ (z_{1}, \dots, z_{n}) \vert z_{i} \in \mathbb{C} \right\}
C n := C n = { ( z 1 , … , z n ) ∣ z i ∈ C }
Hence, v ∈ C Γ v \in \mathbb{C}^{\Gamma} v ∈ C Γ can be seen both as a function similar to v : i ↦ z i v : i \mapsto z_{i} v : i ↦ z i and as an ordered pair like v = ( z 1 , … , z ∣ Γ ∣ ) v = (z_{1}, \dots, z_{\left| \Gamma \right|}) v = ( z 1 , … , z ∣ Γ ∣ ) .
For finite sets Γ 1 \Gamma_{1} Γ 1 and Γ 2 \Gamma_{2} Γ 2 , the tensor product of two vector spaces C Γ 1 \mathbb{C}^{\Gamma_{1}} C Γ 1 and C Γ 2 \mathbb{C}^{\Gamma_{2}} C Γ 2 is defined as the function space (vector space) C Γ 1 × Γ 2 \mathbb{C}^{\Gamma_{1} \times \Gamma_{2}} C Γ 1 × Γ 2 created from the product space Γ 1 × Γ 2 \Gamma_{1} \times \Gamma_{2} Γ 1 × Γ 2 of Γ 1 \Gamma_{1} Γ 1 and Γ 2 \Gamma_{2} Γ 2 .
Definition For finite sets Γ 1 \Gamma_{1} Γ 1 and Γ 2 \Gamma_{2} Γ 2 , the tensor product of two vector spaces C Γ 1 \mathbb{C}^{\Gamma_{1}} C Γ 1 and C Γ 2 \mathbb{C}^{\Gamma_{2}} C Γ 2 is defined as follows.
C Γ 1 ⊗ C Γ 2 : = C Γ 1 × Γ 2
\mathbb{C}^{\Gamma_{1}} \otimes \mathbb{C}^{\Gamma_{2}} := \mathbb{C}^{\Gamma_{1} \times \Gamma_{2}}
C Γ 1 ⊗ C Γ 2 := C Γ 1 × Γ 2
Here, Γ 1 × Γ 2 \Gamma_{1} \times \Gamma_{2} Γ 1 × Γ 2 is the product space of Γ 1 \Gamma_{1} Γ 1 and Γ 2 \Gamma_{2} Γ 2 .
Explanation For a simple example, let’s consider Γ 1 = 2 = { 1 , 2 } \Gamma_{1} = \mathbf{2} = \left\{ 1, 2 \right\} Γ 1 = 2 = { 1 , 2 } and Γ 2 = 3 = { 1 , 2 , 3 } \Gamma_{2} = \mathbf{3} = \left\{ 1, 2, 3 \right\} Γ 2 = 3 = { 1 , 2 , 3 } . And let’s assume Γ \Gamma Γ as their product space.
Γ = Γ 1 × Γ 2 = { ( 1 , 1 ) , ( 1 , 2 ) , ( 1 , 3 ) , ( 2 , 1 ) , ( 2 , 2 ) , ( 2 , 3 ) }
\Gamma = \Gamma_{1} \times \Gamma_{2} = \left\{ (1,1), (1,2), (1,3), (2,1), (2,2), (2,3) \right\}
Γ = Γ 1 × Γ 2 = { ( 1 , 1 ) , ( 1 , 2 ) , ( 1 , 3 ) , ( 2 , 1 ) , ( 2 , 2 ) , ( 2 , 3 ) }
Let’s denote the elements of this as follows.
e i ⊗ e j = ( i , j )
e_{i} \otimes e_{j} = (i, j)
e i ⊗ e j = ( i , j )
Following the logic from the overview, v ∈ C Γ v \in \mathbb{C}^{\Gamma} v ∈ C Γ can be seen as a function like ( i , j ) ↦ α i j (i,j) \mapsto \alpha_{ij} ( i , j ) ↦ α ij and also as an ordered pair like ( α 11 , a 12 , a 13 , a 21 , a 22 , a 23 ) \left( \alpha_{11}, a_{12}, a_{13}, a_{21}, a_{22}, a_{23} \right) ( α 11 , a 12 , a 13 , a 21 , a 22 , a 23 ) . Therefore, C Γ \mathbb{C}^{\Gamma} C Γ is a vector space with { e i ⊗ e j : 1 ≤ i ≤ 2 , 1 ≤ j ≤ 3 } \left\{ e_{i} \otimes e_{j} : 1 \le i \le 2, 1 \le j \le 3 \right\} { e i ⊗ e j : 1 ≤ i ≤ 2 , 1 ≤ j ≤ 3 } as its basis .
C Γ = { ∑ i , j α i , j e i ⊗ e j : α i j ∈ C } = { ( α 11 , a 12 , a 13 , a 21 , a 22 , a 23 ) : α i j ∈ C }
\begin{align*}
\mathbb{C}^{\Gamma} &= \left\{ \sum\limits_{i,j} \alpha_{i,j} e_{i} \otimes e_{j} : \alpha_{ij} \in \mathbb{C} \right\} \\
&= \left\{ \left( \alpha_{11}, a_{12}, a_{13}, a_{21}, a_{22}, a_{23} \right) : \alpha_{ij} \in \mathbb{C} \right\}
\end{align*}
C Γ = { i , j ∑ α i , j e i ⊗ e j : α ij ∈ C } = { ( α 11 , a 12 , a 13 , a 21 , a 22 , a 23 ) : α ij ∈ C }
Hence, it is isomorphic to C 6 \mathbb{C}^{6} C 6 .
C Γ = C 2 ⊗ C 3 ≅ C 6
\mathbb{C}^{\Gamma} = \mathbb{C}^{2} \otimes \mathbb{C}^{3} \cong \mathbb{C}^{6}
C Γ = C 2 ⊗ C 3 ≅ C 6
Grouping C \mathbb{C} C into a product space can be thought of as increasing the position of variables , and grouping into a tensor product as increasing the position of indices .
z 1 ∈ C ( z 1 , z 2 ) ∈ C × C ( z 1 , z 2 , z 3 ) ∈ C × C × C
z_{1} \in \mathbb{C}\qquad (z_{1},z_{2}) \in \mathbb{C} \times \mathbb{C}\qquad (z_{1}, z_{2}, z_{3}) \in \mathbb{C}\times \mathbb{C} \times \mathbb{C}
z 1 ∈ C ( z 1 , z 2 ) ∈ C × C ( z 1 , z 2 , z 3 ) ∈ C × C × C
( z 1 , z 2 ) ∈ C 2 ( z 11 , z 12 , z 21 , z 22 ) ∈ C 2 ⊗ C 2 ( z 111 , z 112 , z 121 , z 122 , z 211 , z 212 , z 221 , z 222 ) ∈ C 2 ⊗ C 2 ⊗ C 2
(z_{1}, z_{2}) \in \mathbb{C}^{2} \qquad (z_{11}, z_{12}, z_{21}, z_{22}) \in \mathbb{C}^{2} \otimes \mathbb{C}^{2} \\[1em]
(z_{111}, z_{112}, z_{121}, z_{122}, z_{211}, z_{212}, z_{221}, z_{222}) \in \mathbb{C}^{2} \otimes \mathbb{C}^{2} \otimes \mathbb{C}^{2}
( z 1 , z 2 ) ∈ C 2 ( z 11 , z 12 , z 21 , z 22 ) ∈ C 2 ⊗ C 2 ( z 111 , z 112 , z 121 , z 122 , z 211 , z 212 , z 221 , z 222 ) ∈ C 2 ⊗ C 2 ⊗ C 2
Each e i ⊗ e j e_{i} \otimes e_{j} e i ⊗ e j corresponds to the standard basis vector of C 6 \mathbb{C}^{6} C 6 as follows.
e 1 ⊗ e 1 = [ 1 0 0 0 0 0 ] e 1 ⊗ e 2 = [ 0 1 0 0 0 0 ] e 1 ⊗ e 3 = [ 0 0 1 0 0 0 ] e 2 ⊗ e 1 = [ 0 0 0 1 0 0 ] e 2 ⊗ e 2 = [ 0 0 0 0 1 0 ] e 2 ⊗ e 3 = [ 0 0 0 0 0 1 ]
e_{1} \otimes e_{1} = \begin{bmatrix}1 \\ 0 \\ 0 \\ 0 \\ 0 \\ 0\end{bmatrix} \quad
e_{1} \otimes e_{2} = \begin{bmatrix}0 \\ 1 \\ 0 \\ 0 \\ 0 \\ 0\end{bmatrix} \quad
e_{1} \otimes e_{3} = \begin{bmatrix}0 \\ 0 \\ 1 \\ 0 \\ 0 \\ 0\end{bmatrix} \\[2em]
e_{2} \otimes e_{1} = \begin{bmatrix}0 \\ 0 \\ 0 \\ 1 \\ 0 \\ 0\end{bmatrix} \quad
e_{2} \otimes e_{2} = \begin{bmatrix}0 \\ 0 \\ 0 \\ 0 \\ 1 \\ 0\end{bmatrix} \quad
e_{2} \otimes e_{3} = \begin{bmatrix}0 \\ 0 \\ 0 \\ 0 \\ 0 \\ 1\end{bmatrix}
e 1 ⊗ e 1 = 1 0 0 0 0 0 e 1 ⊗ e 2 = 0 1 0 0 0 0 e 1 ⊗ e 3 = 0 0 1 0 0 0 e 2 ⊗ e 1 = 0 0 0 1 0 0 e 2 ⊗ e 2 = 0 0 0 0 1 0 e 2 ⊗ e 3 = 0 0 0 0 0 1
When expressed as a Kronecker product of matrices, it looks like this.
e 1 ⊗ e 1 = [ 1 0 ] ⊗ [ 1 0 0 ] = [ 1 [ 1 0 0 ] 0 [ 1 0 0 ] ] = [ 1 0 0 0 0 0 ] e 1 ⊗ e 2 = [ 1 0 ] ⊗ [ 0 1 0 ] = [ 1 [ 0 1 0 ] 0 [ 0 1 0 ] ] = [ 0 1 0 0 0 0 ] e 1 ⊗ e 3 = [ 1 0 ] ⊗ [ 0 0 1 ] = [ 1 [ 0 0 1 ] 0 [ 0 0 1 ] ] = [ 0 0 1 0 0 0 ] e 2 ⊗ e 1 = [ 0 1 ] ⊗ [ 1 0 0 ] = [ 0 [ 1 0 0 ] 1 [ 1 0 0 ] ] = [ 0 0 0 1 0 0 ] e 2 ⊗ e 2 = [ 0 1 ] ⊗ [ 0 1 0 ] = [ 0 [ 0 1 0 ] 1 [ 0 1 0 ] ] = [ 0 0 0 0 1 0 ] e 2 ⊗ e 3 = [ 0 1 ] ⊗ [ 0 0 1 ] = [ 0 [ 0 0 1 ] 1 [ 0 0 1 ] ] = [ 0 0 0 0 0 1 ]
e_{1} \otimes e_{1} = \begin{bmatrix} 1 \\ 0 \end{bmatrix} \otimes \begin{bmatrix} 1 \\ 0 \\ 0 \end{bmatrix}
= \begin{bmatrix} 1 \begin{bmatrix} 1 \\ 0 \\ 0 \end{bmatrix} \\[1.5em] 0 \begin{bmatrix} 1 \\ 0 \\ 0 \end{bmatrix} \end{bmatrix}
= \begin{bmatrix} 1 \\ 0 \\ 0 \\ 0 \\ 0 \\ 0 \end{bmatrix} \quad
e_{1} \otimes e_{2} = \begin{bmatrix} 1 \\ 0 \end{bmatrix} \otimes \begin{bmatrix} 0 \\ 1 \\ 0\end{bmatrix}
= \begin{bmatrix} 1 \begin{bmatrix} 0 \\ 1 \\ 0 \end{bmatrix} \\[1.5em] 0 \begin{bmatrix} 0 \\ 1 \\ 0 \end{bmatrix} \end{bmatrix}
= \begin{bmatrix} 0 \\ 1 \\ 0 \\ 0 \\ 0 \\ 0 \end{bmatrix} \\[2em]
e_{1} \otimes e_{3} = \begin{bmatrix} 1 \\ 0 \end{bmatrix} \otimes \begin{bmatrix} 0 \\ 0 \\ 1 \end{bmatrix}
= \begin{bmatrix} 1 \begin{bmatrix} 0 \\ 0 \\ 1 \end{bmatrix} \\[1.5em] 0 \begin{bmatrix} 0 \\ 0 \\ 1 \end{bmatrix} \end{bmatrix}
= \begin{bmatrix} 0 \\ 0 \\ 1 \\ 0 \\ 0 \\ 0 \end{bmatrix} \quad
e_{2} \otimes e_{1} = \begin{bmatrix} 0 \\ 1 \end{bmatrix} \otimes \begin{bmatrix} 1 \\ 0 \\ 0 \end{bmatrix}
= \begin{bmatrix} 0 \begin{bmatrix} 1 \\ 0 \\ 0 \end{bmatrix} \\[1.5em] 1 \begin{bmatrix} 1 \\ 0 \\ 0 \end{bmatrix} \end{bmatrix}
= \begin{bmatrix} 0 \\ 0 \\ 0 \\ 1 \\ 0 \\ 0 \end{bmatrix} \\[2em]
e_{2} \otimes e_{2} = \begin{bmatrix} 0 \\ 1 \end{bmatrix} \otimes \begin{bmatrix} 0 \\ 1 \\ 0 \end{bmatrix}
= \begin{bmatrix} 0 \begin{bmatrix} 0 \\ 1 \\ 0 \end{bmatrix} \\[1.5em] 1 \begin{bmatrix} 0 \\ 1 \\ 0 \end{bmatrix} \end{bmatrix}
= \begin{bmatrix} 0 \\ 0 \\ 0 \\ 0 \\ 1 \\ 0 \end{bmatrix} \quad
e_{2} \otimes e_{3} = \begin{bmatrix} 0 \\ 1 \end{bmatrix} \otimes \begin{bmatrix} 0 \\ 0 \\ 1 \end{bmatrix}
= \begin{bmatrix} 0 \begin{bmatrix} 0 \\ 0 \\ 1 \end{bmatrix} \\[1.5em] 1 \begin{bmatrix} 0 \\ 0 \\ 1 \end{bmatrix} \end{bmatrix}
= \begin{bmatrix} 0 \\ 0 \\ 0 \\ 0 \\ 0 \\ 1 \end{bmatrix}
e 1 ⊗ e 1 = [ 1 0 ] ⊗ 1 0 0 = 1 1 0 0 0 1 0 0 = 1 0 0 0 0 0 e 1 ⊗ e 2 = [ 1 0 ] ⊗ 0 1 0 = 1 0 1 0 0 0 1 0 = 0 1 0 0 0 0 e 1 ⊗ e 3 = [ 1 0 ] ⊗ 0 0 1 = 1 0 0 1 0 0 0 1 = 0 0 1 0 0 0 e 2 ⊗ e 1 = [ 0 1 ] ⊗ 1 0 0 = 0 1 0 0 1 1 0 0 = 0 0 0 1 0 0 e 2 ⊗ e 2 = [ 0 1 ] ⊗ 0 1 0 = 0 0 1 0 1 0 1 0 = 0 0 0 0 1 0 e 2 ⊗ e 3 = [ 0 1 ] ⊗ 0 0 1 = 0 0 0 1 1 0 0 1 = 0 0 0 0 0 1
Moreover, from this, it can be understood that the following holds.
C ⊗ C n ≅ C n C ⊗ C ≅ C
\mathbb{C} \otimes \mathbb{C}^{n} \cong \mathbb{C}^{n} \qquad \mathbb{C} \otimes \mathbb{C} \cong \mathbb{C}
C ⊗ C n ≅ C n C ⊗ C ≅ C
Properties C n ⊗ C m \mathbb{C}^{n} \otimes \mathbb{C}^{m} C n ⊗ C m is a vector space with respect to the following two operations:( x 1 ⊗ y 1 ) + ( x 2 ⊗ y 2 ) = ( x 1 + x 2 ) ⊗ ( y 1 + y 2 ) (x_{1} \otimes y_{1}) + (x_{2} \otimes y_{2}) = (x_{1} + x_{2}) \otimes (y_{1} + y_{2}) ( x 1 ⊗ y 1 ) + ( x 2 ⊗ y 2 ) = ( x 1 + x 2 ) ⊗ ( y 1 + y 2 ) α ( x ⊗ y ) = ( α x ) ⊗ y = x ⊗ ( α y ) \alpha (x \otimes y) = (\alpha x) \otimes y = x \otimes (\alpha y) α ( x ⊗ y ) = ( αx ) ⊗ y = x ⊗ ( α y ) C n ⊗ C m ≅ C n m \mathbb{C}^{n} \otimes \mathbb{C}^{m} \cong \mathbb{C}^{nm} C n ⊗ C m ≅ C nm dim ( C n ⊗ C m ) = dim ( C n ) ⋅ dim ( C m ) = n m \dim (\mathbb{C}^{n} \otimes \mathbb{C}^{m}) = \dim(\mathbb{C}^{n}) \cdot \dim(\mathbb{C}^{m}) = nm dim ( C n ⊗ C m ) = dim ( C n ) ⋅ dim ( C m ) = nm Generalization For finite sets Γ i ( 1 ≤ i ≤ r ) \Gamma_{i} (1 \le i \le r) Γ i ( 1 ≤ i ≤ r ) , the tensor product of vector spaces C Γ i \mathbb{C}^{\Gamma_{i}} C Γ i is defined as follows.
C Γ 1 ⊗ ⋯ ⊗ C Γ r : = C Γ = C Γ 1 × ⋯ × Γ r , Γ = Γ 1 × ⋯ × Γ r
\mathbb{C}^{\Gamma_{1}} \otimes \cdots \otimes \mathbb{C}^{\Gamma_{r}} := \mathbb{C}^{\Gamma} = \mathbb{C}^{\Gamma_{1} \times \cdots \times \Gamma_{r}},\quad \Gamma = \Gamma_{1} \times \cdots \times \Gamma_{r}
C Γ 1 ⊗ ⋯ ⊗ C Γ r := C Γ = C Γ 1 × ⋯ × Γ r , Γ = Γ 1 × ⋯ × Γ r
The basis vectors corresponding to ( j 1 , … j r ) ∈ ∏ i Γ i (j_{1}, \dots j_{r}) \in \prod\limits_{i} \Gamma_{i} ( j 1 , … j r ) ∈ i ∏ Γ i are denoted as follows: ( 1 ≤ j i ≤ ∣ Γ i ∣ ) ( 1 \le j_{i} \le \left| \Gamma_{i} \right|) ( 1 ≤ j i ≤ ∣ Γ i ∣ )
e j 1 ⊗ ⋯ ⊗ e j r
e_{j_{1}} \otimes \cdots \otimes e_{j_{r}}
e j 1 ⊗ ⋯ ⊗ e j r
Then, the tensor product is a vector space like the following. If the cardinality of Γ i \Gamma_{i} Γ i is denoted by n i = ∣ Γ i ∣ n_{i} = \left| \Gamma_{i} \right| n i = ∣ Γ i ∣ ,
C Γ 1 ⊗ ⋯ ⊗ C Γ r = { ∑ ( j 1 , … j r ) ∈ ∏ i Γ i α j 1 , … , j r e j 1 ⊗ ⋯ ⊗ e j r } = { ( α 1 , … , 1 , … , α n 1 , … , n r ) : α ∈ C } ≅ C ∣ Γ ∣
\begin{align*}
\mathbb{C}^{\Gamma_{1}} \otimes \cdots \otimes \mathbb{C}^{\Gamma_{r}}
&= \left\{ \sum\limits_{(j_{1}, \dots j_{r}) \in \prod\limits_{i} \Gamma_{i}} \alpha_{j_{1}, \dots, j_{r}} e_{j_{1}} \otimes \cdots \otimes e_{j_{r}}\right\} \\
&= \left\{ (\alpha_{1,\dots,1},\ \dots, \alpha_{n_{1},\ \dots, n_{r}}) : \alpha \in \mathbb{C} \right\} \\
&\cong \mathbb{C}^{\left| \Gamma \right|}
\end{align*}
C Γ 1 ⊗ ⋯ ⊗ C Γ r = ⎩ ⎨ ⎧ ( j 1 , … j r ) ∈ i ∏ Γ i ∑ α j 1 , … , j r e j 1 ⊗ ⋯ ⊗ e j r ⎭ ⎬ ⎫ = { ( α 1 , … , 1 , … , α n 1 , … , n r ) : α ∈ C } ≅ C ∣ Γ ∣
General Vector Spaces Given a finite-dimensional vector space V 1 , … , V r V_{1}, \dots, V_{r} V 1 , … , V r , by selecting a basis B i = { v 1 , v 2 , … , v dim V i } \mathcal{B}_{i} = \left\{ v_{1}, v_{2}, \dots, v_{\dim V_{i}} \right\} B i = { v 1 , v 2 , … , v d i m V i } of vector space V i V_{i} V i , one can obtain the following bijection f i f_{i} f i .
f i : V i → C dim V i ∑ z j v j ↦ ( z 1 , … , z dim V i )
\begin{align*}
f _{i}: & V_{i} \to \mathbb{C}^{\dim V_{i}} \\
& \sum z_{j}v_{j} \mapsto (z_{1}, \dots, z_{\dim V_{i}})
\end{align*}
f i : V i → C d i m V i ∑ z j v j ↦ ( z 1 , … , z d i m V i )
Then, the tensor product of V i V_{i} V i is defined as follows.
⨂ i = 1 r V i = V 1 ⊗ ⋯ ⊗ V r : = C dim V 1 ⊗ ⋯ ⊗ C dim V r
\bigotimes\limits_{i=1}^{r} V_{i} = V_{1} \otimes \cdots \otimes V_{r} := \mathbb{C}^{\dim V_{1}} \otimes \cdots \otimes \mathbb{C}^{\dim V_{r}}
i = 1 ⨂ r V i = V 1 ⊗ ⋯ ⊗ V r := C d i m V 1 ⊗ ⋯ ⊗ C d i m V r
See Also